THE IMPACT OF BULLYING ON THE SOCIO-EMOTIONAL DEVELOPMENT OF EARLY CHILDHOOD IN TIRTANADI VILLAGE, EAST LOMBOK - Siska Yuni Lestari (JOETAL: Journal of Education, Teaching and Learning, 2025)
This research was motivated by a deep curiosity about bullying in children aged 4-6 years in Tirpas Tirtanadi Hamlet. Many parents are still unaware of the parenting styles they provide that can lead to children becoming victims of bullying. The purpose of this study was to determine (1) the factors that cause bullying behavior in early childhood in Tirtanadi Village, East Lombok; and (2) the impact of bullying on the social-emotional development of early childhood in Tirtanadi Village, East Lombok. The author used a qualitative research method with a descriptive approach, with children aged 4-6 years in Tirpas Tirtanadi Hamlet as the subjects. The data collection techniques used by the researchers included unstructured interviews, observation, and documentation. The data analysis employed Miles and Huberman's data reduction, data presentation, and conclusion drawing techniques. The results of the study indicate that (1) the factors contributing to bullying behavior in early childhood in Tirtanadi Village, East Lombok are: (a) family factors; (b) peer factors; (c) individual factors. (2) The impact of bullying on the social and emotional development of early childhood in Tirtanadi Village, East Lombok, is: (a) aggressive behavior; (b) emotional instability; (c) low self-confidence; and (d) lack of social skills.